THE ANALYSIS OF ENGLISH SLANGS FOUND IN THE ANTMAN MOVIE - Andri Donal; Andi Rizky Fauzi; Himry Saleh (JEE (Journal of English Education), 2019)
This article discusses the meaning and types of English slangs found in the Ant Man Movie directed by Peyton Reed, produced by Wald Disney Studios Motion Pictures, 2015. The main object of the research was to find out themeaning of English slangs found in the Ant Man Movie and classify themdepending on its characteristics of English Slangs types. This research used a qualitative method. In Classifying the English Slangs, researchers used theory from Coleman that classifying English slangs into seven; English Slang changes in meaning, English Slang changes in function, English Slang change in form, English Slang created by abbreviation, English Slangchanges in spelling, Slangs loans and Slangs from imitating sound. Through this research, researchers found forty English Slangs in the Ant Man Movie; fourteen English Slangs created by changes in meaning, two English Slangs created by changes in, twelve English Slangs created by changes, five English Slangs created by abbreviation, seven English Slangs created bychanges in spelling, four English Slangs loans, and two English Slangs are from sound. English slangs are non-register language. It is more acceptable in daily life because it is fresher and simple in use.